Resiliencia en estudiantes varones y mujeres de bachillerato del colegio Manuela Sáenz de Quito – Ecuador, en tiempos de COVID-19 - Bucheli , José Antonio (2022)
The purpose of the research work was to determine the difference in the level of resilience between male and female high school students at the Manuela Saenz College in the city of Quito-Ecuador in times of COVID-19. The study was of a quantitative approach, descriptive level and non-experimental design, cross-sectional and descriptive comparative; The sample consisted of 112 women and 103 men from high school. The data collection instrument was the Brief Resilience Scale. According to results, in women the medium level of resilience prevailed 53.57% followed by the high level 35.37% and the low level 10.72%, while in men the low level prevailed 46.61% followed by the medium level 38, 83% and high level 14.56%; a significant difference was determined between both groups (p = 0.000). In conclusion, it was shown that female students had a higher level than male students due to a better ability to face adversity.